The Teaching Materials Design of North Sumatran Folktales Based on Augmented Reality - Atika Wasilah; Rosmawaty Rosmawaty; Emasta Evayanti Simanjuntak (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This research is prompted by the students’ low literacy skills in inclusive education in Indonesia, especially in North Sumatra. The current government has given more attention to the implementation of inclusive education through Law Number 8 of 2016 in Article 5 paragraph 3f concerning the persons with disabilities, and Regulation of the Minister of National Education of the Republic of Indonesia Number 70 of 2009 concerning the inclusive education for students who have abnormalities and have potential intelligence and/or special talent. The purpose of this study is to explain the process of developing the augmented reality book of folktales of North Sumatra. The method used in this research is ADDIE (Analysis-Design-Develop-Implement Evaluate) model. One of the functions of ADDIE is as a guide in building training program tools and infrastructure that is effective, dynamic and supports the performance of the training itself. This model uses 5 development stages, they are analysis, design, development, implementation evaluation. This article describes the stages of preliminary study, planning, product development, and product review. The results showed that the steps taken in designing an augmented reality application included: markers on books, reading markers on books, detecting markers, displaying 3D objects and playing sound, and continuing to display 3D objects and sound explanations. Moreover, the architectural design of augmented reality applications includes AR applications.